Gridlock in Global Ocean Governance: Diverging National Interests in the South China Sea - Nappen, Wesley (Perceptions, 2019)
<span data-sheets-value=""1":2,"2":"With the ratification of the United Nations Convention on the Law of the Sea (UNCLOS) in 1994, it was intended to serve as a means of universal ocean governance in resolving international maritime disputes. However, the failure to resolve the ongoing South China Sea Dispute, between the neighboring countries of China, Taiwan, Vietnam, Malaysia, Indonesia, Brunei, and the Philippines, has revealed regulatory gaps on the part of global ocean governance. This paper identifies the origins of gridlock in global ocean governance by identifying the diverging national interests of the actors involved in the South China Sea dispute that hinder cooperation in the region. Furthermore, this paper will show how the legacy of UNCLOS has stifled its own ability to mediate this contemporary conflict. In conclusion, this paper asserts that the key to resolving the South China Sea dispute is through multilateral natural resource extraction between the actors involved in the conflict, aided by the legal and diplomatic support of UNCLOS. "" data-sheets-userformat=""2":515,"3":"1":0,"4":[null,2,65280],"12":0">With the ratification of the United Nations Convention on the Law of the Sea (UNCLOS) in 1994, it was intended to serve as a means of universal ocean governance in resolving international maritime disputes. However, the failure to resolve the ongoing South China Sea Dispute, between the neighboring countries of China, Taiwan, Vietnam, Malaysia, Indonesia, Brunei, and the Philippines, has revealed regulatory gaps on the part of global ocean governance. This paper identifies the origins of gridlock in global ocean governance by identifying the diverging national interests of the actors involved in the South China Sea dispute that hinder cooperation in the region. Furthermore, this paper will show how the legacy of UNCLOS has stifled its own ability to mediate this contemporary conflict. In conclusion, this paper asserts that the key to resolving the South China Sea dispute is through multilateral natural resource extraction between the actors involved in the conflict, aided by the legal and diplomatic support of UNCLOS.